Taurua’s whare - Rangiwai, Byron (Te Kaharoa, 2021)
This paper will discuss Taurua’s whare: a whare built to memorialise Taurua Nātana, his mokopuna, and others and to shelter manuhiri engaged in the pōhiri process at Waiōhau marae. Taurua’s whare is part of the Waiōhau marae complex. The complex includes the wharenui, Tama-ki-Hikurangi—a whare built for the nineteenth-century prophet, Te Kooti (Rangiwai, 2021); a wharemate; a shelter for the paepae; a wharekai named after Te Kooti’s prophecy, Te Umutaoroa;[1] a memorial flagpole, along with three other granite memorials; and a large ablution block. The focal point of the marae complex is the wharenui.